Securing a place for reading in composition : the importance of teaching for transfer - Carillo, Ellen C. (Utah State University Press, 2014)
"Securing a Place for Reading in Composition addresses the dissonance between the need to prepare students to read--not just write--complex texts and the lack of recent scholarship on reading-writing connections. Author Ellen Carillo argues that including attention to reading practices is crucial for developing more comprehensive literacy pedagogies. Students who can read actively and reflectively will be able to work successfully with the range of complex texts they will encounter throughout their post-secondary academic careers and beyond. Considering the role of reading within composition from both historical and contemporary perspectives, Carillo makes recommendations for the productive integration of reading instruction into first-year writing courses. She details a "mindful reading" framework wherein instructors help students cultivate a repertoire of approaches upon which they consistently reflect as they apply them to various texts. This metacognitive frame allows students to become knowledgeable and deliberate about how they read and gives students the opportunity to develop the metacognitive skills useful for moving among reading approaches in mindful ways, thus preparing them to actively and productively read in courses and contexts outside of first-year composition. Securing a Place for Reading in Composition also explores how the field of composition might begin to effectively address reading, including conducting research on reading, revising outcome statements, and revisiting the core courses in graduate programs. It will be of great interest to writing program administrators as well as compositionists"--